Futuristic Design Based on Sustainable Culture and Creative Economy: Material Technology Innovation in Commercial Buildings - I Kadek Pranajaya; Ngurah Gede Dwi Mahadipta; Ni Made Emmi Nutrisia Dewi; Made Eka Wijaya (International Journal of Engineering, Science and Information Technology, 2025)
The integration of futuristic design with sustainable culture and the creative economy offers a transformative paradigm in the development of commercial architecture. This study examines the Dekkson Knowledge Shop as a case study to explore how material technology innovation can address environmental challenges while reinforcing cultural identity and strengthening market competitiveness. Employing a qualitative descriptive method, the research utilizes field observations, in-depth interviews, and documentation analysis to investigate the application of high-performance materials and their interpretation within architectural narratives. The findings highlight that the use of eco-friendly composite panels, fiber-cement boards, and adaptive lighting systems not only enhances energy efficiency and durability but also embeds Balinese cultural values within a futuristic aesthetic framework. A key novelty of this research lies in positioning material technology as a narrative medium that connects modern innovation with cultural sustainability, rather than perceiving it solely as a structural element. This integration enriches user experience, strengthens brand identity, and supports the creative economy by transforming architectural design into a cultural and economic asset. Furthermore, the study proposes a replicable design model for future commercial projects that harmonizes sustainable material innovation with local narratives. The model provides both theoretical contributions to architectural discourse and practical strategies for sustainable design practices applicable in a global context. Through this approach, the research underscores the importance of balancing technological advancement with cultural preservation, thereby establishing commercial architecture as a medium for sustainable innovation, cultural continuity, and economic resilience.